Rapid methods for the genetic determination of pharmacokinetic status - Debenham, Paul (Henry Stewart Talks, 2007)
Key pharmacogenetic targets, Minimizing laboratory processing, Homogenous reactions and DNA probes, Rapid and simple allele discrimination, Point of care
Archived at 2021/02/25